Eryngium horridum como facilitador da comunidade de plantas e artrópodes em campos sob diferentes regimes de distúrbio com fogo e pastejo - Ramos, Kássia (2019)
Facilitation is an important process in structuring communities. A facilitator acts on less competitive species, allowing them to establish in highly competitive environments, especially under disturbances. However, the effects of facilitation are known to be more detectable in environments with harsh conditions, such as sites with disturbance regimes. Disturbances are characterized as events that remove biomass and alter the structure of the environment. The main disturbances that modulate the grasslands ecosystems are fire and grazing. In this work, I used a block experiment to analyze the effect of Eryngium horridum, a plant known as a facilitator for other plants, on the arthropod community in different intensities and types of disturbances. In the first chapter of this dissertation, I present a general introduction to the ecological theory of facilitation and its importance for the grasslands with influence of disturbances. In the second chapter, I present the results of the experimental study on the occurrence of facilitation in the arthropod community and spider assemblage in the grasslands under the influence of fire and grazing. The study was conducted based on an experiment with controlled burning and grazing at the São Lourenço farm, in the city of Santiago, RS. The experiment was conducted in five blocks, each with three plots. Each plot received a type of management (fire, grazing, or fire + grazing) and pairs with two microhabitats (with or without E. horridum) were defined in each management. In each of the microhabitats, I measured the dimensions of vegetation descriptors and soil temperature. In addition, pitffall traps were installed in each plot to capture soil arthropods. Arthropods were identified at class and order level (family in the case of spiders). The spiders were classified according to the foraging strategy. As the main results of chapter 2, I detected a negative effect of E. horridum on soil temperature in all managements, as well as on the richness and abundance of shrubs under grazing + fire. I also observed that E. horridum promoted a positive effect on the height vegetation in all the managements and on the availability of resources and richness of herbaceous under grazing. Already in the arthropod samples, I collected a total of 18,054 individuals, however, only the arthropods that compose the soil macrofauna were used for the analysis, totaling 8,191 individuals. As main results, I observed that management and microhabitat independently influenced the general composition of the community. It was also possible to detect that E. horridum promoted a facilitating effect on the richness of taxa and families of spiders only in the combination of fire and grazing disturbances, which agrees with the main hypothesis of the work, which predicted that E. horridum would have a more important role as facilitator in the environment with greater intensity of disturbance. The results show, for the first time, that facilitation plays an important role in arthropod and plant communities under disturbance regimes, with intensity and type of disturbance dependent responses.